Uncertainties in future energy demand in UK residential heating - Eyre, N; Baruah, P (Elsevier, 2015)
Fossil fuels are the main source of space heating in the UK, and therefore climate mitigation implies a systemic change in space heating systems. The challenge is difficult because of an inefficient building stock and very high penetration of natural gas as a heating fuel. We present new quantified scenarios for residential energy use in the UK to 2050. With minimal policy intervention the UK will remain locked into a gas based heating system, but there is a range of scenarios in which this is avoided. Heat pumps powered by low carbon electricity are an option, but complete reliance on this as a solution raises a number of problems. Greater use of energy efficiency and biomass can also play a significant role. Meeting low carbon heating goals is therefore better conceptualised as reducing reliance on gas rather than necessarily mass electrification. We conclude that the future of UK residential space heating is very uncertain. A continuation of the existing pattern is possible, but would conflict with the current UK policy goal of decarbonisation. UK policy makers’ currently preferred alternative is a system heavily reliant on heat pumps supplied with low carbon electricity. We conclude that some shift in this direction is very likely to be required, but that a very heavy reliance on this approach poses a number of risks. Other approaches, notably greater emphasis on energy efficiency and biofuels, have different risks, but a more diversified strategy would be more prudent until those risks are better understood. Our analysis focusses on the UK, but has implications for any country with high demand for fossil fuels to provide space heating in buildings and ambitious decarbonisation goals.